2018
DOI: 10.3855/jidc.10541
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira in the different ecological niches of the tribal union territory of India

Abstract: Introduction: Leptospirosis is a widespread zoonotic disease, which has a medical and veterinary importance, and also a commonly re-emerging infectious disease. The main causes of transmission are known; however, the respective prominence of each of the components and the respective environmental risk factors are obscure. Methodology: Present study was conducted in the different locations (urban/rural/tribal) of the union territory of Dadra and Nagar Haveli (UT of Dadra and Nagar Haveli). Periodical samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Much higher seropositivity (61.1%) was found among the Irula tribes of Tamil Nadu State, India 13 . In the tribes of Dadra Nagar Haveli, India, 36.5 per cent seropositivity was reported 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Much higher seropositivity (61.1%) was found among the Irula tribes of Tamil Nadu State, India 13 . In the tribes of Dadra Nagar Haveli, India, 36.5 per cent seropositivity was reported 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In urban area, other Leptospira (P1) contamination from water samples were detected in public toilet 66,7% [ 23 ], water canal from slaughterhouse 16,7% [ 29 ], rice field 8,3% [ 26 ], recreational lake 1,7% [ 27 ], open drainage around household between 1,9% − 36% [ 20 , 26 , 28 , 47 , 48 ], human drinking water 8% [ 45 ], household water storage between 4% − 17,2% [ 21 , 24 , 25 ], groundwater and well between 1,6% − 33,3% [ 21 , 22 , 25 , 46 ]. Pathogenic Leptospira (P1) were not detected in industrial drainage [ 48 ], the puddle at slaughterhouses [ 29 ], irrigation and dry canals near the market [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In rural area, pathogenic Leptospira (P1) detected in spring that used for drinking 40% [ 34 ], waterfall 35,3% [ 36 ], river between 2,1%-33,3% [ 19 , 35 , 37 , 38 , 44 , 45 ], well 25,4% [ 46 ], household puddles between 2,2% − 41,1% [ 37 , 39 , 45 ], household water storage 17%-46,7% [ 42 , 45 ], drinking water 9,3%-15% [ 37 , 45 ], drainage from household 2.1% − 6.7% [ 35 , 48 ] and cowshed drainage 13,3% [ 48 ]. There was no contamination detected in the pool, stream, forest land, and river from rural area [ 34 , 48 ]. ( Table 2 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies worldwide have shown a significant correlation between soil chemical properties and the survival of Leptospira bacteria. For example, in India, soil samples from rice fields and nearby stables were highly prevalent for Leptospira compared to urban sites [80]. Similarly, in Australian cane fields, the bacteria can survive up to seven weeks in acidic soil at pH 6.2 and three weeks in the rainwater-flooded soil [81].…”
Section: Leptospira Persistence In the Environmentmentioning
confidence: 99%